PENYIMPANAN ARSIP DINAMIS DEPARTEMEN KESEKRETARIATAN PADA BAGIAN ARSIP PUSAT PT. PINDAD (PERSERO) - Hilwah Hafidzah Muthmainnah (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2020)
Abstrak Tujuan dari tulisan ini adalah untuk mengetahui prosedur dari penyimpanan arsip dinamis departemen kesekretariatan pada bagian Arsip Pusat PT Pindad (Persero) dan kendala apa saja yang dihadapi saat kegiatan penataan dan penyimpanan arsip dinamis pada bagian Arsip Pusat PT Pindad (Persero). Metode yang digunakan adalah melalui pengamatan dan melakukan wawancara dengan pegawai arsip di PT Pindad (Persero). Berdasarkan analisis data, dapat disimpulkan bahwa prosedur penyimpanan arsip tersebut tidak melalui proses pengindeksan, sehingga membutuhkan waktu banyak dalam pencarian kembali, dan tidak menggunakan kode spesifik untuk memudahkan penemuan. Lalu, hambatannya adalah kekurangan Sumber daya manusia dan pegawai arsip yang tidak memiliki latar belakang pendidikan kearsipan, dan gedung penyimpanan yang kurang layak digunakan. Kata Kunci: Arsip, Penyimpanan Arsip, Arsip Dinamis ABSTRACT The purpose of writing this paper is to find out the procedures of dynamic archive storage in the Central Archives section of PT Pindad (Persero), what obstacles and obstacles are encountered when structuring and storing dynamic archive activities in the Central Archives section of PT Pindad (Persero). The method used in this research is qualitative apporach through field observations and by interviewing the archive staff in PT Pindad (Persero). Based on data analysis, it can be concluded that the procedure of dynamic archive storage in the central Archives section of PT Pindad (Persero) is the stages of Archive Inspection, Archive Sorting, Archive Marking, Archive Recording, and finally Archive Storage. Archives are stored in a Folder (Map) and arranged in the Filling Cabinet. Activities that are not carried out in the existing procedures so that it can become an obstacle in the management of the Archives, First, the Archives do not go through the indexing process, so it requires more time when searching back archives. Second, the existing archives only use codes according to the type of letter, do not use specific codes to facilitate the rediscovery of archives. Then, the obstacle that was found was the very lack of human resources in the management of archives, in addition to the employees of the archives who did not have an educational background related to archives and archives, as well as archival storage buildings that were unfit for use to store archives. Keywords: Archive, Archive Storage, Dinamic Archive